WAYS OF FORMING A MANAGEMENT SYSTEM USING BUDGETING IN JOINT STOCK COMPANIES (Marketing Journal, 2025)
This article discusses ways to form an effective management system using budgeting mechanisms in joint -stock companies. In addition, the article analyzes the integration of budgeting with strategic planning, control and analysis processes, as well as the m anagement model based on the created economic value added (EVA) and balanced scorecard (BSC), and provides practical suggestions for the formation of control mechanisms through the budget committee of the enterprise management, the RACI matrix, the budgeti ng calendar, and ERP systems.
Keywords: budgeting; corporate governance; created economic value added (EVA); balanced scorecard (BSC); RACI matrix; strategic planning; ERP system. 345